2012
DOI: 10.1111/cup.12043
|View full text |Cite
|
Sign up to set email alerts
|

BerEP4 is widely expressed in tumors of the sweat apparatus: a source of potential diagnostic error

Abstract: This case and pilot study shows that BerEP4 expression is common in these selected sweat apparatus tumors, and staining may be strongly so. This observation should be borne in mind in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The lesion was characterised by ulceration, necrosis, and cells with pleomorphic nuclei and mitotic activity. One area of the tumour had cells with cytoplasmic vacuoles and this area stained positively for CK7, supporting the presence of ductal differentiation and the diagnosis of a primary cutaneous adnexal neoplasm ( Qureshi et al, 2004 ), and BerEP4, which is commonly expressed in sweat gland tumours and in particular, in porocarcinomas ( Afshar et al, 2013 ). The patient was referred to a Gynaecological Oncologist who performed a wide local excision of the scar.…”
Section: Case Reportmentioning
confidence: 69%
“…The lesion was characterised by ulceration, necrosis, and cells with pleomorphic nuclei and mitotic activity. One area of the tumour had cells with cytoplasmic vacuoles and this area stained positively for CK7, supporting the presence of ductal differentiation and the diagnosis of a primary cutaneous adnexal neoplasm ( Qureshi et al, 2004 ), and BerEP4, which is commonly expressed in sweat gland tumours and in particular, in porocarcinomas ( Afshar et al, 2013 ). The patient was referred to a Gynaecological Oncologist who performed a wide local excision of the scar.…”
Section: Case Reportmentioning
confidence: 69%
“…18 In addition, several other sweat gland tumors, sebaceous tumors, and Merkel cell carcinoma exhibit varying degrees of c-KIT immunoexpression. 18 BerEP4 has a tendency to be positive in porocarcinoma 20 but negative in SCC; however, no previous studies have investigated the utility of BerEP4 in the differential diagnosis of porocarcinoma and SCC. Our study revealed that the sensitivity for BerEP4 in porocarcinoma (8/14, 57.1%) was not high, and only 2 (9.1%) of 22 SCC cases, both of which were vulvar tumors, showed limited expression of BerEP4.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, there are still a few other potential immunohistochemical markers such as BerEP4 and GATA3 that have not been well investigated for the differential diagnosis. [20][21][22] The purpose of this study was to compare these immunohistochemical markers and to establish the best immunohistochemical method for distinguishing porocarcinoma from SCC.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, although BerEP4 is expressed by nearly all BCCs, 22,23 it is also expressed by some poromas and porocarcinomas (usually focally). 24 Therefore, traditional staining of the poroid ducts with EMA and/or CEA is an important highlight in the differential diagnosis. 25 …”
Section: Discussionmentioning
confidence: 99%